12.0k views
2 votes
Prove that P (P) = (QA ~ Q)] is a tautology.

User JBallin
by
4.3k points

1 Answer

2 votes

Answer:

The statement
P \leftrightarrow [(\lnot P) \rightarrow (Q \land \lnot Q)] is a tautology.

Explanation:

A tautology is a formula which is "always true" that is, it is true for every assignment of truth values to its simple components.

To show that this statement is a tautology we are going to use a table of logical equivalences:


P \leftrightarrow [(\lnot P) \rightarrow (Q \land \lnot Q)] \equiv


\equiv (P \land [(\lnot P)\rightarrow (Q \land \lnot Q)]) \lor(\lnot P \land \lnot [(\lnot P)\rightarrow (Q \land \lnot Q)]) by the logical equivalences involving bi-conditional statements


\equiv (P \land [\lnot(\lnot P)\lor (Q \land \lnot Q)]) \lor(\lnot P \land \lnot [\lnot(\lnot P)\lor (Q \land \lnot Q)]) by the logical equivalences involving conditional statements


\equiv (P \land [P\lor (Q \land \lnot Q)]) \lor(\lnot P \land \lnot [ P\lor (Q \land \lnot Q)]) by the Double negation law


\equiv (P \land [P\lor (Q \land \lnot Q)]) \lor(\lnot P \land \lnot P\land \lnot(Q \land \lnot Q)) by De Morgan's law


\equiv (P \land [P\lor F]) \lor(\lnot P \land \lnot P\land \lnot(Q \land \lnot Q)) by the Negation law


\equiv (P \land [P\lor F]) \lor(\lnot P \land \lnot P\land \lnot Q \lor \lnot(\lnot Q)) by De Morgan's law


\equiv (P \land [P\lor F]) \lor(\lnot P \land \lnot P\land \lnot Q \lor  Q) by the Double negation law


\equiv (P \land P) \lor(\lnot P \land \lnot P\land \lnot Q \lor  Q) by the Identity law


\equiv (P) \lor(\lnot P \land \lnot P\land \lnot Q \lor  Q) by the Idempotent law


\equiv (P) \lor(\lnot P \land \lnot P\land  (Q\lor \lnot Q)) by the Commutative law


\equiv (P) \lor(\lnot P \land \lnot P\land T) by the Negation law


\equiv (P) \lor(\lnot (P \lor P)\land T) by De Morgan's law


\equiv (P) \lor(\lnot (P)\land T) by the Idempotent law


\equiv (P \lor\lnot P) \land(P \lor T) by the Distributive law


\equiv (T) \land(P \lor T) by the Negation law


\equiv (T) \land(T) by the Domination law


\equiv T

Prove that P (P) = (QA ~ Q)] is a tautology.-example-1
User Vijay Kahar
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.